2007
DOI: 10.1262/jrd.18156
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Cyclic AMP Levels and Phosphodiesterase Activities in the Rat Ovary

Abstract: Abstract. Cyclic AMP (cAMP) is a second messenger that plays a critical role in follicular recruitment, development and luteinization in the mammalian ovary. The cellular level of cAMP is largely dependent on the activity of phosphodiesterase (PDE), which degrades cAMP into 5'-AMP. The present study was conducted to investigate the level of cAMP and the activity of cAMP-PDE in postnatal rats; immature rats during gonadotropin-primed follicular development, ovulation and luteinization; adult rats during normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
4
14
0
1
Order By: Relevance
“…In agreement with the present results, treatment of immature rats with eCG increased both cAMP levels and PDE activities in ovarian homogenates (Wang et al 2007), and gonadotropin stimulation caused the activation of PDE via an increase in cAMP in cultured Sertoli (Conti et al 1982) and granulosa cells (Conti et al 1984). Further studies demonstrated that TSH quickly activated the cAMP-specific PDE in the thyroid cells through a phosphorylation mediated by the catalytic subunit of PRKA (Sette et al 1994).…”
Section: Puberty and Oocyte Meiotic Resumptionsupporting
confidence: 91%
“…In agreement with the present results, treatment of immature rats with eCG increased both cAMP levels and PDE activities in ovarian homogenates (Wang et al 2007), and gonadotropin stimulation caused the activation of PDE via an increase in cAMP in cultured Sertoli (Conti et al 1982) and granulosa cells (Conti et al 1984). Further studies demonstrated that TSH quickly activated the cAMP-specific PDE in the thyroid cells through a phosphorylation mediated by the catalytic subunit of PRKA (Sette et al 1994).…”
Section: Puberty and Oocyte Meiotic Resumptionsupporting
confidence: 91%
“…Our morphological examination showed that typical histological changes were consistent with those observed in our previous report (Wang et al, 2007). At postnatal day 1, the ovary contained only primordial follicles with an oocyte partially or completely encapsulated by squamous pre-granulosa cells ( Figure 1A), and HIF-1α immunoreactivities were markedly localized to the oocytes ( Figure 1B).…”
Section: Follicular Development and Hif-1α Immunohistochemistry In Thsupporting
confidence: 89%
“…1) Postnatal rat model (Wang et al, 2007): neonatal rats were obtained by mating adult Sprague-Dawley males and females. After birth, neonatal rats at 1, 5, 7, 10, and 21 days of age (the day of birth was considered day 1) were sampled under ether anesthesia, and the ovaries were immediately collected.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of bound radioactivity was determined by γ counting. The caMP level of each sample was measured using commercial ria kits as previously described (12).…”
Section: Methodsmentioning
confidence: 99%